Impact of Menstrual Attitudes, Premenstrual Syndrome, and Stress Response on Quality of Life among Nursing Students - Hee Jin Jang; Mi Hae Sung (Korean Society of Women Health Nursing, 2018)
PURPOSE: To identify effects of menstrual attitude, premenstrual syndrome, and stress response on quality of life of nursing students. METHODS: Subjects were 135 nursing students who agreed to participate in this study. Data were analyzed using descriptive statistics, t-test, ANOVA, Pearson correlation, and stepwise multiple regression. RESULTS: Premenstrual syndrome, younger than 20 years of age, and habit of eating bland food in everyday life were factors influencing quality of life of nursing students. These factors accounted for 17.6% of quality of life. Premenstrual syndrome toward quality of life was the most influential factor. CONCLUSION: Premenstrual syndrome is the most significant factor affecting the quality of life of nursing students. To increase their quality of life, it is important to develop and apply educational programs using factors influencing quality of life of the nursing students. Results of this study will be useful as basic data for improving quality of life of nursing students. Additional study is needed to test its effect in the future.